Interleukin 18 messenger RNA and proIL-18 protein expression in chorioamniotic membranes from pregnant women with preterm prelabor rupture of membranes - Polettini, Jossimara [UNESP]; Vieira, Eliane Passarelli [UNESP]; Santos, Mariana Perlati dos [UNESP]; Peraçoli, José Carlos [UNESP]; Witkin, Steven Sol [UNESP]; Silva, Marcia da [UNESP] (Elsevier B.V., 2012)
Objective: To quantify the expression of IL-18 mRNA and protein in the chorioamniotic membranes of pregnant women with PPROM and correlate expression with histological chorioamnionitis.Study design: A case control study that included 42 pregnant women not in labor in the following groups: PPROM (n = 28) and controls with intact membranes submitted to selective cesarean section at term (n = 14). Expression of IL-18 mRNA in chorioamniotic membranes was determined by real-time polymerase chain reaction, and IL-18 protein expression was measured by western blot. Histopathological analyses and immunolocalization of IL-18 by immunohistochemistry were also performed. Analyses were performed using the Mann-Whitney or Fisher's exact tests and the group effect was considered significant if the adjusted p-values were <0.05 and the magnitude of change was greater than 2-fold for mRNA expression.Results: IL-18 mRNA was present in 100% of samples and no difference in expression was observed between term vs. PPROM membranes (fold-change 0.12; p = 0.88). In the PPROM group, no difference was observed in IL-18 mRNA regarding gestational age (fold-change 0.11; p = 0.42) or the presence of histological chorioamnionitis (fold-change 0.26; p = 0.15). ProIL-18 was present in all samples. IL-18 was immunolocalized to amnion, chorion and decidua cells, with intense immunohistochemical staining at the choriodecidual junction.Conclusion: Chorioamniotic membranes are sources of IL-18 mRNA and proIL-18, and their expression is unrelated to PPROM or histological chorioamnionitis.
Keywords: Preterm prelabor rupture of membranes; Interleukin-18; proIL-18; Histological chorioamnionitis